Konsep Pelaksanaan Keputusan Tata Usaha Negara: Menguji Asas Presumtio Iustae Causa Dalam Sengketa Tata Usaha Negara - Sukri, Indah Fitriani; Erliyana, Anna (UI Scholars Hub, 2022)
In the implementation of the State Administration Decree (KTUN), the principle of presumtiousta causa is known as part of the implementation of the KTUN in order to resolve state administrative disputes. This principle means a state administration decision which is always considered valid. This decision will be invalid if there are new decisions that cancel or revoke the previous decisions. In its formation, the administrative court or state administration court has the objective to provide protection for the rights of the people derived from individual rights as well as to protect the rights of the community based on the common interests of individuals in the community. The government has an obligation to advance the general welfare stated in the constitutional mandate. In carrying out this decision, the government carries out administrative and enforcement law.